2019
DOI: 10.21203/rs.2.12799/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Obesity, Diabetes and the Risk of Colorectal Adenoma and Cancer

Abstract: Background: Colorectal cancer (CRC) is the fourth most commonly diagnosed gastrointestinal (GI) malignancy and the third leading cause of cancer-related death worldwide. In the current case-control study, an association between diagnosis of CRC, obesity and diabetes was investigated. Methods: Demographic characteristics, colonoscopy reports, history of drug, smoking, and medical history were collected from patients referred to a colonoscopy unit. The location, size and number of the polyps were recorded durin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 40 publications
0
17
0
5
Order By: Relevance
“…Colon adenocarcinoma (COAD) is one of the most common gastrointestinal (GI) cancers and is the second leading cause of cancer-related death, globally [ 1 , 2 ]. It is demonstrated that COAD occurs in approximately 5% of overall population at any given time in the world [ 3 ]. Despite the current screenings and therapies such as endoscopic resection and radical surgery, nearly half of the patients are diagnosed as advanced cases of COAD, experiencing tumor recurrence and relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Colon adenocarcinoma (COAD) is one of the most common gastrointestinal (GI) cancers and is the second leading cause of cancer-related death, globally [ 1 , 2 ]. It is demonstrated that COAD occurs in approximately 5% of overall population at any given time in the world [ 3 ]. Despite the current screenings and therapies such as endoscopic resection and radical surgery, nearly half of the patients are diagnosed as advanced cases of COAD, experiencing tumor recurrence and relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the adenoma detection rate (27%) is this study is similar to large population colonoscopy study (19.4%). 23 Given the retrospective nature, the other risk factors such as diabetes mellitus, 24 hyperlipidemia, 25 smoking, family history of colorectal cancers 26 and use of aspirin/non-steroidal antiinflammatory drugs 14 were not investigated. These factors have been well studied in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Here is their definition: mean average precision (AP): AP: AP at IoU = 0:50 : 0:05 : 0:95 (primary challenge metric), AP 50 : AP at IoU = 0:50, AP 75 : AP at IoU = 0:75, AP S : AP for small objects: area < 32 2 , AP M : AP for medium objects: 32 2 < area < 96 2 , AP L : AP for large objects: area > 96 2 . Average recall (AR): AR: AR given 1 detection per image, AR 10 : AR given 10 detections per image, AR 100 : AR given 100 detections per image, AR S : AR for small objects: area < 32 2 , AR M : AR for medium objects: 32 2 < area < 96 2 , AR L : AR for large objects: area > 96 2 . The results are shown in Table 2.…”
Section: Performance Of Mask R-cnn Modelmentioning
confidence: 99%
“…With the improvement of Chinese people's living standards, the incidence of CRC increases year by year. The most common precancer disease of CRC is colorectal adenoma (CRA) [2]. At present, total colonoscopy is still the best screening method for colorectal polyps, CRA, and CRC [3].…”
Section: Introductionmentioning
confidence: 99%